1996
DOI: 10.1088/0953-8984/8/39/005
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamical conductivity in icosahedral boron-rich solids

Abstract: The FIR spectra of boron-rich solids measured down to 10 cm −1 exhibit strongly increasing reflectivities towards lower frequencies. These spectra are well described when a superposition of Drude-type and hopping-type dynamical conductivity is assumed. The corresponding fits were simultaneously made for the real and the imaginary part of the dielectric function to achieve unambiguous parameters. The results obtained can be described consistently, for example, with DC conductivity measurements, and moreover in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…The parameters determined by fitting the optical spectra (for the complete set see (19)) are to be compared with other experimental results. At first, the squared plasma frequency , which is proportional to the density of Drude-type-free carriers, is compared in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters determined by fitting the optical spectra (for the complete set see (19)) are to be compared with other experimental results. At first, the squared plasma frequency , which is proportional to the density of Drude-type-free carriers, is compared in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, XPS measurements also indicated significant amounts of O and Fe in the films, which was discussed elsewhere. 13 XPS also indicated that there is no appreciable difference in composition between room-temperature-and 573 K-deposited AlMgB 14 films. The microstructure of AlMgB 14 films, which was examined by transmission electron microscopy, 12 remains amorphous regardless of substrate temperature, and no evidence of conducting inhomogeneities or crystalline domains was observed.…”
mentioning
confidence: 96%
“…Compared with the electrical resistivity of other boron-rich boride films, which typically cover a wide range of values from ϳ10 3 to 10 9 ⍀ cm, the electrical resistivity of room-temperature-and 573 K-deposited AlMgB 14 films is approximately three to eight orders of a)…”
mentioning
confidence: 98%
See 2 more Smart Citations